1962
DOI: 10.1111/j.1570-7458.1962.tb00569.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RESPIRATION OF INSECTS AT REDUCED PRESSURES: I. THE EXPIRATION OF CARBON DIOXIDE BY TENEBRIOIDES MAURITANICUS (L.)

Abstract: Carbon dioxide expiration of larvae of Tenebrioides mauritanicus (L.) exposed to reduced pressures in air is increased temporarily during the initial period of change from atmospheric pressure down to 35 mm Hg. During this time there is evidence of irritation of the insects shown by increased locomotor activity. After the required low pressure is reached the insects soon assume an activity and CO2 expiration characteristic for that pressure. At 35 mm, the lowest pressure attainable before fatal desiccation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Subsequently, in a study of the respiration of T. mauritmicus at reduced pressures (Monro, Dumas and Buckland 1962), it was found that in the range of reduced pressures where mortality was low the rate of respiration was also low.…”
mentioning
confidence: 99%
“…Subsequently, in a study of the respiration of T. mauritmicus at reduced pressures (Monro, Dumas and Buckland 1962), it was found that in the range of reduced pressures where mortality was low the rate of respiration was also low.…”
mentioning
confidence: 99%